Self-Efficacy of Providers of Early Intervention Services to Young Children with Visual Impairments and Their Families. (March 2020) - Ely, Mindy S.; Ostrosky, Michaelene M.; Burke, Meghan M.
Introduction: Anthony cautions that the training of teachers of students with visual impairments (i.e., blindness and low vision) and orientation and mobility (O&M) specialists covers a broad age range, which may result in limited curricular content essential for those who will work with very young children with visual impairments. The current study focuses on the self-efficacy of vision professionals regarding their work with infants and toddlers in using evidence-based approaches found in the early childhood literature. Methods: Teachers and O&M specialists ( n = 109) from 11 states participated in a survey of perceptions of self-efficacy and working with infants and toddlers with visual impairments. Correlates of preparedness, experience, vision-specific self-efficacy, and early intervention self-efficacy were investigated. Results: Participants indicated that they felt inadequately trained to work with infants and toddlers. Self-efficacy measures regarding motivation to implement vision-specific recommended practices were higher than motivation to implement early intervention practices; however, self-efficacy measures for early intervention confidence and practice were higher than vision-specific confidence and practice. Although participants' ratings of the vision training program they attended were not correlated with their own self-efficacy measures, the amount of early childhood education content reported by participants was significantly correlated with all self-efficacy measures. Further, experience was correlated with self-efficacy. Discussion: Results support the need for a greater emphasis on early intervention content in visual impairment training programs. Additionally, the fact that half of the respondents in this study were over 50 years of age suggests that a turnover in personnel is imminent. Inevitably, this new workforce will lack experience. Information for practitioners: Professional preparedness that includes a strong foundation in recommended practices in early childhood will strengthen the workforce and should ultimately improve services to infants and toddlers with sensory disabilities and their families. Practitioners may need to seek out this specialized training.